Identificación de las áreas de importancia hídrica en el piso bioclimático bspno1 de 300 a 1400 msnm dentro del proyecto de investigación “Recuperación de germoplasma de especies vegetales de la zona nor-occidental” en la parroquia El Tingo, cantón Pujilí, provincia de Cotopaxi 2018. - Vargas German, Miriam Paulina (2018)
The research was carried out in El Tingo Parish, Pujilí Canton, Cotopaxi Province, the primary objective of this study was to identify the areas of importance of water recharge to ensure the sustainability of natural resources and especially water, it was important delimited the water basin and the bioclimatic floor BsPn01 from 300 to 1400 meters above sea level, which generated important information from the study area since there was little information generated in the sector. The researcher used the commercial software ArcGis 10.2, it is a GIS tool that helped to facilitate the execution of operations and analysis between layers of information to observe the spatial distribution of the results, such as slopes, areas of importance of water recharge which make possible to propose measures of conservation of existing species in the study area. Also, it allowed to visualize and generate a map which will clearly show the location of the study site. The use of GIS is a fundamental technology for hydrographic management since it facilitates calculations with greater precision and less time. To identify the main areas of water recharge, the RAS method was used which consists of preparing water recharge maps by means of climatic balance, slopes, temperature and rainfall, as well as proposed measures for the management and conservation of the water resource, which will provide relevant information as a basis for further research on water recharge.